Determination of ethanol in acetic acid-containing samples by a biosensor based on immobilized Gluconobacter cells - ANATOLY N. RESHETILOV; ANNA E. KITOVA; ALENA V. ARKHIPOVA; VALENTINA A. KRATASYUK; MAHENDRA K. RAI (Smujo International, 2012)
Abstract. Reshetilov AN, Kitova AE, Arkhipova AV, Kratasyuk VA, Rai MK. 2012. Determination of ethanol in acetic acid containing samples by a biosensor based on immobilized Gluconobacter cells. Nusantara Bioscience 4: 97-100. A biosensor based on Gluconobacter oxydans VKM B-1280 bacteria was used for detection of ethanol in the presence of acetic acid. It was assumed that this assay could be useful for controlling acetic acid production from ethanol and determining the final stage of the fermentation process. Measurements were made using a Clark electrode-based amperometric biosensor. The effect of pH of the medium on the sensor signal and the analytical parameters of the sensor (detection range, sensitivity) were investigated. The residual content of ethanol in acetic acid samples was analyzed. The results of the study are important for monitoring the acetic acid production process, as they represent a method of tracking its stages.